Contingency, cognitive and semiotic approaches to decision-making in the organizations - A. A. Kulinich (Открытое образование (Москва))
The purpose of this work consists in the conceptual analysis of a current state and the practical importance of some approaches to decision-making in the conditions of uncertainty. The article shows the approaches to decision-making in poorly defined and semistructured situations (objects, organizations), descriptions are presented in a linguistic kind in the form of expert knowledge, value judgment and hypothetical assumptions. Contingency, cognitive and semiotic approaches to support of decision-making in such cases are considered.The material statement is based on the analysis of the Russian and foreign scientific publications under the considered approaches in the historical aspect. In the beginning the approach description in a statement of its founders is carried out. Then the short review, significant from the author’s point of view, modern theoretical and practical works in a considered direction in Russia and abroad is presented. Further the author’s point of view, concerning advantages, lacks, constructiveness and prospects of the considered approach is presented.The analysis result is the basic ideas in a general view, a current state, an estimation of the practical importance of the considered approaches to decision-making. These results can be useful to developers of systems of decision-making support and lecturers of higher educational institutions as a methodical material in processes of students’ training in decisionmaking and artificial intellect areas.